TravelLog Application: A Structured Mobile Travel Documentation Solution Utilizing Firebase Realtime Database - Syamsuddin, Maulida Hamida; Nugraha, Adnan; Shodiq, Naufal Fajar; Lestary, Fitriyanty Dwi (Journal of Security, Computer, Information, Embedded, Network, and Intelligence System, 2025)
The TravelLog application was developed to address the need for structured travel documentation, utilizing Firebase Realtime Database for instant data synchronization. This study aimed to create a mobile application enabling users to log travel details, manage destination wishlists, and access records easily through search and filter features. Employing the Agile methodology, the development process was conducted iteratively, emphasizing intuitive UI/UX design and Black Box testing to ensure functionality. The results demonstrate that TravelLog effectively overcomes the limitations of conventional documentation methods, such as physical notes or unorganized photo galleries, providing an integrated, efficient, and user-friendly solution.